The spread of intangible cultural heritage in the rural agricultural environment of modern China under the epidemic economic environment - Xuanyi, Wu; Yasin, Megat Al Imran; Abdullah, Karmilah; Fan, Zhao; Zhao, Yanmei; Wenling, Li; Huaqiang, Li (University of Missouri, Columbia, 2023)
In the rural agricultural environment, intangible cultural heritage has proved to be a resilient and essential component of community identity and well-being, especially in the face of the challenges posed by the epidemic economic environment. The preservation and celebration of intangible cultural practices, such as traditional agricultural methods, local festivals, and folk arts, provide opportunities for community connection, pride, and economic development despite the economic recession. The current financial crisis threatens China's rural agricultural communities' intangible cultural assets and long-term viability. Using awareness (as a mediator) and access to resources (as a moderator), this study examines how the expansion of intangible cultural assets and the rural agricultural environment affects preservation and sustainability in modern China's rural agricultural environments during the economic epidemic. A simple random sampling technique was used to collect information from 430 participants. Smart-PLS was employed to assess the dependability of data and the relationship between factors. The results indicate that disseminating intangible cultural heritage and the rural agricultural environment is advantageous to preserving intangible cultural heritage and the viability of rural communities. Moreover, resource access regulates and modulates this link. According to the study, increasing awareness and providing access to resources can help rural communities preserve intangible cultural assets and nurture long-term development.